2014
DOI: 10.1002/clen.201300524
|View full text |Cite
|
Sign up to set email alerts
|

4‐Phenyl‐3‐thiosemicarbazide Modified Magnetic Nanoparticles: Synthesis, Characterization and Application for Heavy Metal Removal

Abstract: A novel magnetic nano‐adsorbent has been synthesized by the covalent immobilization of poly (acrylic acid) (PAA) and a ligating agent 4‐phenyl‐3‐thiosemicarbazide (TSC) on the surface of Fe3O4 nanoparticles. The prepared magnetic nanoparticles (MNPs) were characterized by scanning electron microscopy (SEM), atomic force microscopy, vibrating sample magnetometer, Fourier transform infrared spectroscopy and X‐ray diffraction analysis. The SEM images showed that the diameters of the Fe3O4@PAA@TSC MNPs are about 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Synthetic chelating ion exchange resins are receiving considerable attention because of their application in different areas such as the removal of toxic metals, heterogeneous catalysis, solid electrolytes, ion exchange membrane, ion selective electrode, and purification of drinking water and industrial wastewaters . In recent years, the development of high performance adsorbents in nanoscale for removal of toxic metal ions from aqueous solutions and other applications is considered a research priority in the wide fields . Nanotechnology has been able to deliver a wide range of new materials.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic chelating ion exchange resins are receiving considerable attention because of their application in different areas such as the removal of toxic metals, heterogeneous catalysis, solid electrolytes, ion exchange membrane, ion selective electrode, and purification of drinking water and industrial wastewaters . In recent years, the development of high performance adsorbents in nanoscale for removal of toxic metal ions from aqueous solutions and other applications is considered a research priority in the wide fields . Nanotechnology has been able to deliver a wide range of new materials.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetism modification of chitosan can be effectively used for solid‐liquid separation and regeneration of the adsorbents in the removal of heavy metals from wastewater . The functionalization of magnetic chitosan nanoparticles with thiosemicarbazide (TSC) can introduce more nitrogen and sulfur binding sites to the adsorbents, which can chelate heavy metal ions via coordination reaction and improve the adsorption capacity …”
Section: Introductionmentioning
confidence: 99%
“…Chemical and physical properties (such as charge, size, and bonding ability) of the pollutant particles determine the chemical structures of the active sites. 16,17 For the removal of heavy metal ions from aqueous solutions, commonly, the active sites include the functional groups such as carboxyl, hydroxyl, amine, sulfide, thiol, and amide. 18,19 It have been demonstrated that nanocomposites containing active sites with soft-donor groups such as amine and sulfide are one of the best choices for effective removal of heavy metal ions from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 It have been demonstrated that nanocomposites containing active sites with soft-donor groups such as amine and sulfide are one of the best choices for effective removal of heavy metal ions from aqueous solutions. 16,17 These nanoadsorbents form reversible complexes with heavy metal cations and, hence, can remove them in the presence of interfering species such as phosphate anions and alkaline earth metal cations. 16,18 Interfering ions can occupy active sites of the adsorbents and, hence, reduce their capacity for the removal of target ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation